Diskursus Regulasi dan Kebijakan Pendidikan Islam di Indonesia - Ritonga, Matnur; Dede Rosyada (EduInovasi: Journal of Basic Educational Studies, 2024)
An Islamic educational institution is a place where education within the scope of Islam carries out its duties in order to achieve the ideals of Muslims. Family, mosque, majelis taklim, diniyah, madrasa, and Islamic boarding schools are Islamic educational institutions that are absolutely necessary in Indonesia in general or in a city and village area in particular. Comprehensive religious education is needed to instill appropriate moral values for the legal community in order to understand the implementation of religious rules correctly and precisely. The method used is descriptive qualitative through literature review. The results of the study show that; 1. There is a clear history and red thread of regulation regarding Islamic education in Indonesia, the development of Islamic education, and the implications of Islamic education policy for the existence of Islamic boarding schools and religious education in Indonesia. 2. Islamic education policy in Indonesia has undergone changes since the Old Order to the New Order, with an increase in the status of religious education in public schools and universities. 3. Islamic education in Indonesia has experienced significant changes and developments since the 2000s. Islamic boarding schools have adopted the formal education system, and some boarding schools have opened universities. However, the increase in the number of Islamic boarding schools has not been accompanied by an increase in quality. Law No. 18/2019 on Pesantren is expected to recognize and facilitate the development of pesantren and religious education.